The Advantages of Online Recruitment and Selection: A Systematic Review of Cost and Time Efficiency - Arman, Md (Business Management and Strategy, 2023)
This article aims to discuss the benefits of online recruitment and selection in organizations. The research shows how the key benefits of online recruitment and selection can be taken and used for the company’s interest by finding the right person for the right job. This paper tends to content analysis focusing on the benefits of online recruitment process using meta-data. The present trends of recruitment and selection process is very unexpected. Additionally, the characteristics of online recruitment sites are also discussed briefly to illustrate a complete overview of newly formed recruitment system though the primary objective of the paper is to demonstrate the superiority of time and money saving approach. The researcher took social media to exemplify, describing both pros and cons, the present recruiting system. However, there are also some drawbacks to online recruitment and selection which are addressed in this paper. Online recruitment and selection can be a valuable tool for companies looking to reach a wider pool of candidates and streamline the recruitment process. It is important to be aware of the potential drawbacks and take steps to mitigate them in order to ensure the best results. Using meta-analysis, the researcher scratched the advantages of online recruitment and selection process. This paper indicates how the online recruitment process should be done in organizational practice.